A Review on Antiplasmodial Activities of Hyptis suaveolens Plant - Dauda Danlami; Ruqayyah Hamidu Muhammad; Kabir Mustapha Umar (Kwaghe International Journal of Sciences and Technology, 2026)
Hyptis suaveolens (L.), a member of the Lamiaceae family, has long been used in traditional medicine and has recently attracted increasing attention for its antimalarial potential. This review synthesizes existing evidence on the antimalarial properties of H. suaveolens, with particular emphasis on its bioactive constituents, including flavonoids, terpenoids, and essential oils, which have demonstrated notable activity against malaria parasites. Evidence from both in vitro and in vivo studies indicates that extracts of H. suaveolens can inhibit Plasmodium species, particularly Plasmodium falciparum, the major causative agent of human malaria. The review further examines the proposed mechanisms underlying these effects, including inhibition of parasite growth, cytotoxic activity, and immunomodulatory responses. In addition, it highlights key challenges that must be addressed for therapeutic development, notably the standardization of plant extracts, clarification of toxicity profiles, and the need for rigorous clinical trials. Overall, the review underscores the promise of H. suaveolens as a potential source of novel antimalarial agents and contributes to ongoing efforts to identify plant-based alternatives for malaria treatment.